Study of Human Cystic Echinococcosis in Hyderabad, Pakistan: Human Cystic Echinococcosis in Hyderabad - Murtaza, Lochi Ghulam; Shah, Muhammad Ghiasuddin; Merani, Amjad Hussain; Khan, Muhammad Shoaib; Khushk, Sheeraz Mustafa; Khokhar, Abdul Manan (Biological Sciences - PJSIR, 2013)